Soroprevalência de Helicobacter pylori em pacientes com adenomas de cólon - Matoso, Abadia Gilda Buso (2007)
Helicobacter pylori is a risk factor for chronic gastritis, gastroduodenal ulcer and gastric cancer. The association between this infection and colon neoplasia has been the reason for recent investigations which have produced controversial results. The objective of this study was to evaluate the prevalence of H. pylori infection in patients with colonic adenomas and also in patients whose colonoscopy exams were normal. After colonoscopy, the individuals were distributed into two groups: patients with colon adenomas (cases) and patients whose colons were normal (controls). The groups were similar regarding age and gender. The individuals of both groups were subjected to a dosage of IgG antibody against H. pylori. The dosage was applied according to the solid phase, chemiluminescent immunometric assay. The chi-square test was used to analyze the data. There were 30 men and 64 women in each group (94 cases and 94 controls). The mean age of the cases was 59.79 ± 12.25 years and that of the controls was 58.98 ± 11.55 years. The H. pylori serology was positive for 66 (70.21%) of the cases and for 51 (54.25%) of the controls. There was a significant difference (p=0.024). The odds ratio was 1.98 (CI 95%, 0.82 3.15). The prevalence of H. pylori in cases and controls according to gender, histological type and location of the colon lesions showed a significant difference only among women (p=0.030), among patients with tubular adenomas (p=0.030), and in those with distal adenomas (p=0.038). In until sixty-years old patients and in older it was observed a bigger H. pylori seroprevalence compared to control group, but with no significant difference (p=0.068 e p=0.161, respectively). It was concluded that there is a positive association between H. pylori infection and colonic adenomas. This association is more evident in women, especially for tubular adenomas and distal colonic location.